Effects of exercise training on growth and physiology of large-mouth bass (Micropterus salmoides) reared in a recirculating aquaculture system - Ji, Mingdong; Li, Haijun (Frontiers in Marine Science, 2024)
Large-mouth bass originally lived in rivers and lakes and now is often raised in recirculating aquaculture systems (RAS). However, the shortcoming of RAS is that there is very limited space for swimming fish in a high-density culture environment, thus leading to a lack of exercise. To investigate the effects of exercise training on growth performance, digestive enzymes, stress, and antioxidant capacity of large-mouth bass in a RAS, three training water flow velocities with three replicates were used in the present study: low water velocity: 0.5 body length per second (bl/s) (LV); medium water velocity: 1 bl/s (MV); and high water velocity: 1.5 bl/s (HV). 270 large-mouth bass (average initial body weight 47.51 ± 1.44 g, initial body length 12.71 ± 0.06 cm) were randomly divided into nine tanks (30 fish per tank). After 27 days experiment, the results showed that the growth performance of large-mouth bass, including feed intake, weight gain rate, and specific growth rate, in the HV group was significantly higher compared to the other groups. On the physiological level, the lipase and amylase activities were significantly increased in the HV group compared to the other groups. For the stress response parameters, the cortisol, glucose and lactate concentrations in the HV group were significantly increased, which may indicate higher stress in the HV group. Regarding the antioxidant enzyme activities, the activities of catalase (CAT) and glutathione peroxidase (GSH-PX) in the LV group were significantly higher than those in the HV group, which indicated that fish suffered higher oxidative stress in the LV group. Regarding the immune-related parameters, LZM and ACP activities had no significant differences among the groups, while AKP activities in the MV and HV groups were significantly higher than that in the LV group. Overall, the results demonstrated that exercise training had significant effects on the growth, digestion, stress, and immune response of large-mouth bass. It is suggested that exercise training with 1.5 bl/s can enhance fish growth, however, it also presents a potential risk of inducing stress in fish. Therefore, in rearing large-mouth bass in RAS, the setting of water flow velocity should not only focus on the growth of large-mouth bass but also consider its welfare.